The Palladium‐Catalyzed Carboxytelomerization of Butadiene with Agrobased Alcohols and Polyols. Issue 11 (17th May 2019) - Wilson, Emma; Dumont, Clément; Drelon, Mathieu; Suisse, Isabelle; Penverne, Christophe; Sauthier, Mathieu
Abstract: The palladium catalyzed carboxytelomerization reaction of alcohols with butadiene allows for efficient and atom‐economical access to unsaturated alkyl nona‐3, 8‐dienoate esters. The study focused on the nature of the catalyst (phosphine and acid) with ethanol. Commercially available triarylphosphines and carboxylic acids associated with a simple palladium precursor appear to be the best combination for in situ generation of the catalyst. The reaction conditions were further optimized and the carboxytelomerization reaction was efficiently applied to the full transformation of several industrially relevant agro‐based monoalcohols and polyols. Abstract : Efficient & economical : The one‐pot catalytic synthesis of unsaturated esters from agro‐based alcohols and polyols is explored using a palladium‐catalyzed carboxytelomerization reaction with butadiene. The method allows for efficient and atom‐economical access to the corresponding alkyl nona‐3, 8‐dienoate esters.